BS EN IEC 61300-3-27. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Part 3-27. Examinations and measurements. Method for measurement of guidehole and fibre hole/core position of rectangular ferrules (14th October 2019) - British Standards Institution,
No abstract available